Synthesis and Photoswitching Properties of Liquid Crystals Derived from Myo-Inositol - Lutfor, M. R.; M. M., Yusoff; Kumar, Sandeep (Royal Society of Chemistry, 2014)
A new series of unconventional liquid crystal molecules derived from myo-inositol core were synthesized by linking six azobenzene units having terminal double bonds as polymerizable functional groups to myoinositol. Differential scanning calorimetry, polarizing optical microscopy and X-ray diffraction studies were carried out to determine mesomorphism in these materials. Thus, all compounds showed stable enantiotropic SmA phase which was independent of the chain length and chain parity. The photoswitching behaviour of these molecules in solutions showed E to Z isomerization in 8–10 s, whereas the reverse process took about 270–305 min. In solid film, the E–Z photoisomerization took 5 s, while the reverse transformation from Z to E state took 120 min. The photoswitching behaviour of these materials represents one of the fastest switching times so far observed in such materials and,therefore, they are good candidates for molecular switches.